Pengaruh Kecepatan Putaran Kompresor Terhadap Produktivitas Unit Desalinasi Berbasis Pompa Kalor Dengan Proses Humidifikasi dan Dehumidifikasi - Indri Yaningsih (JURNAL MECHANICAL, 2014)
This study was conducted to examine the effect of the compressor rotation speed on the productivity of a desalination unit based heat pump with using humidification and dehumidification process. Desalination unit consists of a heat pump system, humidifier and dehumidifier, and seawater heater and air heater (condenser). In this study, the compressor rotation speed was varied at 500 rpm, 700 rpm and 900 rpm, using a variable frequency inverter that mounted on an electric motor driving the compressor. Research parameters were kept constant i.e. the seawater mass flow rate entering the humidifier at 0.086 kg/s, the temperature of seawater entering the humidifier was kept constant at 45oC, the air velocity entering the humidifier constant at 4 m/s, salinity seawater feed at 31,342 ppm, and seawater in the system was recirculated. The results of this study show that the production of freshwater increases with increasing the compressor rotation speed. The average of freshwater production rate of the desalination unit for the compressor rotation speed of 500 rpm, 700 rpm and 900 rpm were 20.33 l/day, 22.20 l/day, and 24.48 l/day, respectively. Keywords : compressor rotation, dehumidification, desalination, heat pump, humidification